Comparison analysis of the magnetic field and the magnetic force inside of an electromagnetic actuator with the use of an armature measuring sensor - Heyder, Andreas; Losch, T.; Meyer, Alexander Wilhelm; Abersfelder, Sandra; Franke, Jörg (2016 6th International Electric Drives Production Conference, EDPC 2016 - Proceedings, 2016)
Common errors in electromagnetic actuators must be reduced in order to meet the increasing requirements in quality and manufacturing costs. In-line magnetic process control is a promising method to avoid a great number of errors in early stages of production. This paper displays the meaningful correlation between the magnetic field and magnetic force characteristics of a proportional magnet. For this investigation, an armature measuring sensor is developed and implemented into a magnetic field test bench, which enables the realization of a so called smart factory.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electromagnetic actuator; in-line measurement; magnetic process control; three-dimensional magnetic field measurement

Concept for Magnet Intra Logistics and Assembly Supporting the Improvement of Running Characteristics of Permanent Magnet Synchronous Motors - Meyer, Alexander Wilhelm; Heyder, Andreas; Kühl, Alexander; Sand, Christian; Gehb, Hermann; Abersfelder, Sandra; Franke, Jörg; Holzhey, Rocco; Buettner, Ulrich; Wangemann, Sebastian (Procedia CIRP, 2016)
Current scientific studies prove the dependency of the running characteristics of permanent magnet synchronous motors on variations of the physical properties of permanent magnets and manufacturing errors. Currently, this fact is not considered in most process chains for magnet and rotor assembly. Thus, insufficient rotor quality can only be detected during the end-of-line test, causing rejects of whole motors. As a solution for these drawbacks, a computerized magnet intra-logistics storage and assembly concept is presented, using sophisticated magnet measurement technologies. This concept allows for the traceability of single magnets and enables to compensate variations of the magnetic properties by selective magnet assembly.
CRIS-Team Scopus Importer:2023-03-07
Keywords: magnet assembly; magnetic tolerancing; PMSM; tolerancing; traction drives

Crack detection in PM-rotors using magnetic field measurement and data processing - Abersfelder, Sandra; Meyer, Alexander Wilhelm; Heyder, Andreas; Herzog, Moritz; Franke, Jörg; Brela, Matthaeus (2017 7th International Electric Drives Production Conference, EDPC 2017 - Proceedings, 2018)
Electric drives efficiency is determined by the mechanical and magnetic properties of the functional elements stator and rotor. Focus element for this investigation is the rotor including its permanent magnets. Due to several manufacturing influences the properties of those magnets vary considerably. Magnet failures that can occur during manufacture are cracks, blowholes or inclusions, which can lead to commutation problems or to increased noise [1]. Crack propagation is a long-lasting process and cause unintentional failure in field. Currently no automated quality inspection of micro cracks is available in electric drive production. Consequently, the challenge is to develop reliable and safe process concept, to separate bad from good rotors based on magnetic field measurements in order to detect failures at the internal or external assembled magnets. For this purpose, a data analyzing method was developed to identify and characterize micro cracks in already assembled permanent magnets.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Actuators and System Integration; Crack Detection; Data Processing; Fault Detection; Magnetic Field Measurement; Permanent Magnet; Sensors

Magnetic stray field measurement of magnetic specimen - Heyder, Andreas; Tenner, M.; Meyer, Alexander Wilhelm; Abersfelder, Sandra; Franke, Jörg (2016 6th International Electric Drives Production Conference, EDPC 2016 - Proceedings, 2016)
The production of electromagnetic actuators is a complex procedure with a great number of potential influences on the process and hence the quality of the final product itself. The necessity for an in-line magnetic production system which allows an efficient monitoring of the magnetic properties of work pieces at different stages of the production process thus becomes apparent.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electromagnetic actuator; in-line measurement; magnetic process control; magnetic stray field measurement; test bench development; three-dimensional magnetic field measurement

Optimization of a servo motor manufacturing value stream by use of 'Industrie 4.0' - Abersfelder, Sandra; Heyder, Andreas; Franke, Jörg (2015 5th International Conference on Electric Drives Production, EDPC 2015 - Proceedings, 2015)
'Industrie 4.0' establishes multidirectional ways of cross-linking in the production area. Therefore, a complex integration of horizontal and vertical interactions has to work hand in hand. A closer look into present production shows a huge amount of optimization potentials on the way to a 'Smart Factory' with high product variability. Hence, one of the next milestones for production is to create a virtual image of the real products in the manufacturing execution system (MES) in order to have a gapless traceability and an extensive storage of process data along the whole value chain. Especially data mining will gain importance to scan information for meaningful correlations or creating configuration rules as well as decisions for subsequent process steps. For a servo motor production the implementation of a magnetic field measurement of rotors is an opportunity to gather data for data mining. In addition to that, other interesting benefits are expected in failure detection, quality improvement and an increase in performance. To evaluate the different mentioned areas of activity, a pilot test series is planned. It will also provide data sets for a first data mining investigation. The concept of the first rotor measurement test procedure is presented in the following.
CRIS-Team Scopus Importer:2023-03-07
Keywords: 'Industrie 4.0'; Magnetization; Servo Motors

Prediction of electric motor performance by in-line testing of permanent excited rotors - Abersfelder, Sandra; Meyer, Alexander Wilhelm; Heyder, Andreas; Thanner, Marius; Franke, Jörg (2016 6th International Electric Drives Production Conference, EDPC 2016 - Proceedings, 2016)
The market growth of electric drives is pushed forward due to high coercive magnet material and new, more efficient motor designs. These new designs require only small tolerances within the whole manufacturing process. While quality assurance is well established within the stator manufacturing process, the rotor assembly process suffers from lack of testing. Hence, this gap causes rejects not detected until the end-of-line-test of the whole motor, measuring especially the back electromotive force (BEMF) and the total harmonic distortion (THD) of the output signal. To avoid rejects of whole motors at the end of the value chain, this paper presents the possibilities delivered by in-line magnetic field measuring of the rotor. Therefore, different testing methods, such as a commercial available monolithic hall array and a discrete hall line array are used and evaluated. Out of these measurement series a rotor KPI is defined in order to evaluate the rotor quality right after the measurement.
CRIS-Team Scopus Importer:2023-03-07
Keywords: BEMF; hall measurement; manufacturing tollerances; permanent magnet; synchronous motor